EXIT OF SENIOR AGE COHORTS FROM THE RUSSIAN LABOUR MARKET: A SURVIVAL ANALYSIS APPROACH - Irina A. Denisova (Население и экономика, 2017)
The paper examines individual exit trajectories of Russians from the labour market to economic inactivity using survival analysis methods based on the Russian Longitudinal Monitoring Survey for 1995-2015. The analysis shows that the statutory retirement age (55 for women and 60 for men) has a significant impact on the time of exit from the labour market for both sexes, but the effect is significantly higher for women, and the differences are statistically significant: the hazard rate of exit to inactivity rises by 63 percentage points when a woman reaches 55 years of age, but by only 25 percentage points when a man reaches 60.Russiashows some differences in occupational patterns of exit to pension-age inactivity: unlike many developed countries, only highly skilled staff remain in the labour market longer than others, while there is no statistically significant difference between the behaviour of middle-skilled staff and of skilled and unskilled workers. Self-employment and entrepreneurship postpone exit to inactivity as does employment at state enterprises.